Regulatory function of the endogenous hormone in the germination process of quinoa seeds - Zeng, Fang; Zheng, Chunmei; Ge, Wenxuan; Gao, Ya; Pan, Xin; Ye, Xueling; Wu, Xiaoyong; Sun, Yanxia (Frontiers in Plant Science, 2024)
The economic and health significance of quinoa is steadily growing on a global scale. Nevertheless, the primary obstacle to achieving high yields in quinoa cultivation is pre-harvest sprouting (PHS), which is intricately linked to seed dormancy. However, there exists a dearth of research concerning the regulatory mechanisms governing PHS. The regulation of seed germination by various plant hormones has been extensively studied. Consequently, understanding the mechanisms underlying the role of endogenous hormones in the germination process of quinoa seeds and developing strategies to mitigate PHS in quinoa cultivation are of significant research importance. This study employed the HPLC-ESI-MS/MS internal standard and ELISA method to quantify 8 endogenous hormones. The investigation of gene expression changes before and after germination was conducted using RNA-seq analysis, leading to the discovery of 280 differentially expressed genes associated with the regulatory pathway of endogenous hormones. Additionally, a correlation analysis of 99 genes with significant differences identified 14 potential genes that may act as crucial "transportation hubs" in hormonal interactions. Through the performance of an analysis on the modifications in hormone composition and the expression of associated regulatory genes, we posit a prediction that implies the presence of a negative feedback regulatory mechanism of endogenous hormones during the germination of quinoa seeds. This mechanism is potentially influenced by the unique structure of quinoa seeds. To shed light on the involvement of endogenous hormones in the process of quinoa seed germination, we have established a regulatory network. This study aims to offer innovative perspectives on the breeding of quinoa varieties that exhibit resistance to PHS, as well as strategies for preventing PHS.